Metastatic gallbladder carcinoma presenting as an ovarian mass - Nidhin Rehman; Harish Sadashiva; Manoj Gopal Madakshira; Deep Kumar Raman (University of São Paulo, 2021)
Metastatic gallbladder carcinoma to the ovaries is occasional but a recognized entity. It can mimic, clinical and morphologically, a primary ovarian tumor, challenging the diagnosis. We present the case of a patient with a lump in the hypogastrium extending into the right iliac fossa and was found to have abdominopelvic cystic lesion with enhancing solid components and multiple sub-centimetric and ill-defined abdominal lymph nodes. Also, subpleural and parenchymal nodules in the lungs were present. She subsequently underwent a laparotomy. Cholecystectomy was also done due to pre-existing symptomatic biliary lithiasis. The histologic report described the ovarian involvement as metastases from a gallbladder carcinoma. The presentation of ovarian metastases can challenge the diagnosis. Hence, careful evaluation of the digestive tract and judicious use of immunohistochemistry should be considered in patients presenting with ovarian masses.